2014
DOI: 10.1016/j.ijsu.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Relaparotomy in colorectal cancer surgery – Do any factors influence the risk of mortality? A case controlled study

Abstract: Patients after relaparotomy for complications of colorectal cancer surgery are at very high risk of mortality. Particularly male gender, older age, poor general condition and anastomotic complications are the risk factors of high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
2
5
1
6
Order By: Relevance
“…In the present study an overall postoperative 30-day mortality rate of 2⋅4 per cent was observed for all patients, comparable with previous population-based studies 11,12,23 -25 evaluating mortality risk in patients undergoing elective colorectal cancer resection (1⋅8-3⋅5 per cent). Previous reported relaparotomy rates after surgery for colorectal cancer range from 5⋅8 to 7⋅2 per cent 26 , in accordance with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study an overall postoperative 30-day mortality rate of 2⋅4 per cent was observed for all patients, comparable with previous population-based studies 11,12,23 -25 evaluating mortality risk in patients undergoing elective colorectal cancer resection (1⋅8-3⋅5 per cent). Previous reported relaparotomy rates after surgery for colorectal cancer range from 5⋅8 to 7⋅2 per cent 26 , in accordance with the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In some cases, the presence of AL results in an increased percentage of surgical reinterventions in order to treat complications such as generalized peritonitis. According to Mik et al [ 21 ], anastomotic failure strongly influences the incidence of re-laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Релапаротомію визначають як повторне розкриття черевної порожнини у перші 60 днів після хірургічного втручання на органах черевної порожнини. Релапаротомія, проведена у першу 21 добу після хірургічного втручання, визначається як рання релапаротомія, після 21 добипізня [3]. Найбільш частою причиною ранніх релапаротомій є ускладнення, пов'язані з першою операцією, такі як кровотеча, перитоніт, евентерація, а причиною пізніх релапаротомійзлукова кишкова непрохідність [1, 3,5,6].…”
Section: матеріали та методи дослідженьunclassified
“…Це свідчить про необхідність подальшого удосконалення як технічних аспектів оперативних втручань,так і антибактеріальної терапії QUESTIONS OF GASTROINTESTINAL TRACT інтраабдомінальної інфекції. Наші дані співпадають з даними літератури [2,3,4,5].…”
Section: матеріали та методи дослідженьunclassified